Professional judgements and decisions on placement in foster care and reunification in Portugal. Issue 2 (4th March 2018) - Carvalho, João M. S.; Delgado, Paulo; Benbenishty, Rami; Davidson-Arad, Bilha; Pinto, Vânia S.
ABSTRACT: This study aims to analyse professional judgements and decisions made in the Portuguese child care system in face of a case vignette of child maltreatment. Using the approach proposed by Benbenishty et al. [(2015). Decision making in child protection: An international comparative study on maltreatment substantiation, risk assessment and interventions recommendations, and the role of professionals' child welfare attitudes. Child Abuse & Neglect, 49, 63–75. doi:10.1016/j.chiabu.2015.03.015], we assessed the decisions of professionals, such as to place the child in foster care or reunify her with her family, on the basis of a series of judgements (e.g. substantiation of alleged abuse and neglect, risk assessments) that are influenced by the characteristics of the case, the decision-making context, and mother's and child's wishes. We conclude that there are different approaches to the case based on different professionals' attitudes that can be classified in two groups: one more pro-removal and the other anti-removal. These groups presented different risk assessments and intervention recommendations, and their decisions where significantly influenced by the mother's and child's wishes. Furthermore, we have done comparisons with studies made in other countries, concluding that the country context can be an important factor that leads to different outcomes. Implications for both practice and research are presented.